On the potential of the Cluster Ion Counter (CIC) to observe local new particle formation, condensation sink and growth rate of newly formed particles - M. Kulmala; M. Kulmala; M. Kulmala; S. Tuovinen; S. Mirme; S. Mirme; P. Koemets; P. Koemets; L. Ahonen; Y. Liu; H. Junninen; T. Petäjä; et al. (Aerosol Research, 2024)
The Cluster Ion Counter (CIC) is a simple three-channel instrument designed to observe ions in the electrical mobility equivalent diameter range from 1.0 to 5 nm. With the three channels, we can observe concentrations of both ion clusters (sub-2 nm ions) and intermediate ions. Furthermore, as derived here, we can estimate condensation sink (CS), intensity of local new particle formation, growth rate of newly formed particles from 2 to 3 nm and formation rate of 2 nm ions. We compared CIC measurements with those of a multichannel ion spectrometer, the Neutral cluster and Air Ion Spectrometer (NAIS), and found that the concentrations agreed well between the two instruments, with correlation coefficients of 0.89 and 0.86 for sub-2 nm and 2.0–2.3 nm ions, respectively. According to the observations made in Hyytiälä, Finland, and Beijing, China, the ion source rate was estimated to be about two to four ion pairs cm−3 s−1. The new CIC is a simple and cheap instrument that can be used in different environments to obtain information about small ion dynamics, local intermediate ion formation and CS in a robust way when combined with the theoretical framework presented here.